2013
DOI: 10.1073/pnas.1220843110
|View full text |Cite
|
Sign up to set email alerts
|

Transitions to catalytically inactive conformations in EGFR kinase

Abstract: The epidermal growth factor receptor (EGFR) is a key protein in cellular signaling, and its kinase domain (EGFR kinase) is an intensely pursued target of small-molecule drugs. Although both catalytically active and inactive conformations of EGFR kinase have been resolved crystallographically, experimental characterization of the transitions between these conformations remains difficult. Using unbiased, all-atom molecular dynamics simulations, we observed EGFR kinase spontaneously transition from the active to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

21
216
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 191 publications
(239 citation statements)
references
References 46 publications
21
216
1
Order By: Relevance
“…PKA belongs to the AGC family of kinases, which are typically characterized by a cis-regulatory C-terminal tail (20). Recently multiple-microsecond timescale simulations have been performed on several tyrosine kinases (21)(22)(23)(24), and a Markov model was constructed for activation of Src kinase that Significance Protein kinases represent a critically important family of regulatory enzymes. Their activity can be altered by mutations and binding events distant from the active site.…”
mentioning
confidence: 99%
“…PKA belongs to the AGC family of kinases, which are typically characterized by a cis-regulatory C-terminal tail (20). Recently multiple-microsecond timescale simulations have been performed on several tyrosine kinases (21)(22)(23)(24), and a Markov model was constructed for activation of Src kinase that Significance Protein kinases represent a critically important family of regulatory enzymes. Their activity can be altered by mutations and binding events distant from the active site.…”
mentioning
confidence: 99%
“…Structural studies also showed an extensive hydrogen-bond network accompanied by reduced hinge flexibility in zeta-chain-associated protein kinase 70 (ZAP-70), which was proposed to maintain the kinase-inactive form (30). Finally, molecular dynamics calculations suggested local unfolding of the hinge in the catalytic domain of epidermal growth factor receptor (EGFR), which was proposed as an intermediate step toward the transition from the inactive to the active state (31,32). However, in contrast to FGFR2, ZAP-70, and EGFR, the X-ray structures of ERK2 show no significant conformational changes around the hinge upon phosphorylation (4,5).…”
Section: Discussionmentioning
confidence: 99%
“…Cracking is inherently difficult to probe experimentally but there are cases when its occurrence has been inferred from simulations. Proteins suggested to undergo cracking include Adk (Whitford et al 2007(Whitford et al , 2008, epidermal growth factor receptor (Shan et al 2013), calmodulin (Tripathi & Portman, 2009) and influenza hemagglutinin . Here we will briefly summarize the computational results for Adk and cracking in relation to a reaction coordinate linking open (inactive) and closed (active) states.…”
Section: Cracking or 'Order-disorder-order' Transitionsmentioning
confidence: 99%